Community Domain and Work-Family Enrichment: an Exploratory Study - Hassan, Zaiton; Kartini Abang Ibrahim, Dayang; Fatihah Abdullah Bandar, Nur; Sabil, Surena; Norsyamimi Md Nor, Nik (International Journal of Engineering and Technology, 2018)
Recently, the positive side of work-family interface, work-family enrichment has been highlighted.  However,   most research  came from Western cultural context and mostly focus on work and family domain only. Therefore, this study aims to investigate community domains demands and resources  and its relationship to  work-family enrichment in the Eastern cultural context, i.e. Malaysia.   Self-administered questionnaire were answered by 506  employees  from six organizations. It was found that family-work enrichment (FWE) is higher than work-family enrichment (WFE).   Resources from neighbors and relatives were positively related to WFE and FWE.   Interestingly, friends’ resources were negatively related to WFE and FWE. The findings strengthened the link between resources and enrichment. This study has shown that support outside the workplace, particularly from relatives and neighbours are important in enhancing work-family and family work enrichment. Thus,  organizations in collectivist society should create community supportive culture to enhance the experience of  work family enrichment among the employees.